Gaya Bahasa Sarkasme pada Akun Media Sosial Tiktok - Biringkanae, Andi Cindy Batari; Garim, Idawati; Nurhusna, Nurhusna (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2024)
This research aims to describe the form and function of sarcasm on Tiktok social media accounts. This type of research is qualitative using descriptive methods. Data collection will be in October 2023. The instrument in this human interest. Data collection techniques in this research used listening, note-taking and documentation techniques. Data analysis uses data analysis techniques based on Miles and Huberman, namely in the form of data reduction, data validity, and drawing conclusions. The results of the research show that the forms of sarcasm language style on the Tiktok social media account include nature sarcasm, epithet sarcasm, action sarcasm, sarcasm resulting from actions and appeal sarcasm. Apart from that, the function of sarcasm language style on the Tiktok social media account is as a form of conveying information, conveying affirmation, conveying opinions, conveying questions, and conveying similarities.